Analysis Of Application Of Discharge Planning In Hypertension Patients On Patient Satisfaction Level - Wilastri M. Alitonang (Chakra Brahmanda Lentera Institute, 2020)
Hypertension is a symptom of an increase in blood pressure, which will be sustained in the target organs, such as stroke, coronary heart disease and right vertebral hypertrophy. Increased arterial blood pressure can increase the risk of kidney failure, heart disease commonly called atherosclerosis is also a stroke. The Purpose of Analyzing Discharge Planning Implementation in Hypertension Patients on Patient Satisfaction Level in Mokoyurli Hospital Buol District. The design used in this study is cross-sectional analytic. The population is all hypertensive patients was 35 respondents. The sample size is 35 respondents using purposive sampling technique. Independent Variable of research is Discharge Planning. The dependent variable is Satisfaction. Data was collected using a questionnaire, then the data were analyzed using the Spearman rho test, with a significance level of α 5 0.05. he results showed that most respondents had sufficient satisfaction as many as 19 respondents (54.3%), more than half of respondents had an adequate Discharge Planning assessment of 20 respondents (57.1%). The results showed that p = 0,000 with a = 0,05, which means that H0 is rejected and H1 is accepted so that it can be interpreted that there is a relationship between Discharge planning in Patients with Hypertension on Patient Satisfaction Level at Mokoyurli Mokoyurli Hospital Buol District, with a correlation coefficient of 0.768 which means having a relationship strong.. Discharge planning can increase knowledge with the need for behavioral changes, and take measures to prevent hypertension and ultimately patient satisfaction with services increases.